Literarische Ausdrucksmittel bei der Übersetzung von Werbung aus didaktischer Perspektive. Literariness of the advertisement in the translation training. - Fišer, Zbyněk (Glottodidactica, 2016)
The author shows the methods, technics and principles of the developing oft the translatory competences on the concrete translation of the advertisement with the outstanding intertextuality. His didactic model of the transtatory training gives accent on the unambiguous definition of the target recipient of the advertisement and the connection both of them the esthetic and persuasive functions in the target text for the target culture, which is impossible without the creative mind and creative language performance of the translator.